Pancreatic α Cells are Resistant to Metabolic Stress-induced Apoptosis in Type 2 Diabetes - Laura Marroqui; Matilde Masini; Beatriz Merino; Fabio A. Grieco; Isabelle Millard; Christine Dubois; Ivan Quesada; Piero Marchetti; Miriam Cnop; Decio L. Eizirik (EBioMedicine, 2015)
Pancreatic α cells are exposed to metabolic stress during the evolution of type 2 diabetes (T2D), but it remains unclear whether this affects their survival. We used electron microscopy to search for markers of apoptosis and endoplasmic reticulum (ER) stress in α and β cells in islets from T2D or non-diabetic individuals. There was a significant increase in apoptotic β cells (from 0.4% in control to 6.0% in T2D), but no α cell apoptosis. We observed, however, similar ER stress in α and β cells from T2D patients. Human islets or fluorescence-activated cell sorting (FACS)-purified rat β and α cells exposed in vitro to the saturated free fatty acid palmitate showed a similar response as the T2D islets, i.e. both cell types showed signs of ER stress but only β cells progressed to apoptosis. Mechanistic experiments indicate that this α cell resistance to palmitate-induced apoptosis is explained, at least in part, by abundant expression of the anti-apoptotic protein Bcl2l1 (also known as Bcl-xL).